PERKEMBANGAN DAN REPRODUKSI CROCIDOLOMIA PAVONANA (F.) (LEPIDOPTERA: PYRALIDAE) PADA PAKAN ALAMI DAN SEMIBUATAN - Novalia Jelita Sari dan Djoko Prijono . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2004)
Development and reproduction of Crocidolomia pavonana (F.) (Lepidoptera: Pyralidae) on natural and artificial diets. Development and reproduction of Crocidolomia pavonana on natural and artificial diets were studied in the laboratory (25.2 ± 0.9 ï‚°C; 84.6% ± 6.7% RH; ca. 12 h photophase). The natural diets tested were broccoli, cabbage, chinese cabbage, and cauliflower leaves. The artificial diets used were agar–based general lepidopteran diets mixed with red bean or broccoli leaves, and supplemented with vitamins and microbial inhibitors. Observation of insect development was done since the egg stage. After the eggs hatched, larvae were kept singly in plastic cups and fed with appropriate diets. Fifty larvae were used for each diet. Records were kept with regard to the duration of each larval instar, pupal period, and the pupal weight. The emerging adults were paired, and then the number of dead adults and that of eggs laid were recorded daily. On all the natural diets tested, the larval stage of C. pavonana passed through four instars. The egg incubation, total larval developmental, and pupal period of C. pavonana on chinese cabbage were the shortest compared to those on the other natural diets. The pupal weight, however, was the highest on broccoli, followed by that on chinese cabbage, cabbage, and cauliflower. The female fecundity was also the highest on broccoli (average 258 eggs/female) followed by that on chinese cabbage (212), cauliflower (162), and cabbage (102). Broccoli diet also yielded adults with the longest lifespan although the adult lifespan on broccoli was not significantly different from that on the other natural diets, except that of males on cabbage. C. pavonana failed to develop successfully on six kinds of artificial diets tested. The best artificial diet (broccoli–based diet with microbial inhibitors 20% of the normal amount) only yielded two males and five females with deformed wings, but none of the emerging females produced eggs.